Accelerated aging and lifetime prediction: Review of non-Arrhenius behaviour due to two competing processes - Celina, M.; Gillen, K.T.; Assink, R.A. (Polymer degradation and stability, 2005)
Lifetime prediction of polymeric materials often requires extrapolation of accelerated aging data with the suitability and confidence in such approaches being subject to ongoing discussions. This paper reviews the evidence of non-Arrhenius behaviour (curvature) instead of linear extrapolations in polymer degradation studies. Several studies have emphasized mechanistic variations in the degradation mechanism and demonstrated changes in activation energies but often data have not been fully quantified. To improve predictive capabilities a simple approach for dealing with curvature in Arrhenius plots is examined on a basis of two competing reactions. This allows for excellent fitting of experimental data as shown for some elastomers, does not require complex kinetic modelling, and individual activation energies are easily determined. Reviewing literature data for the thermal degradation of polypropylene a crossover temperature (temperature at which the two processes equally contribute) of ∼83 °C was determined, with the high temperature process having a considerably higher activation energy (107–156 kJ/mol) than the low temperature process (35–50 kJ/mol). Since low activation energy processes can dominate at low temperatures and longer extrapolations result in larger uncertainties in lifetime predictions, experiments focused on estimating E a values at the lowest possible temperature instead of assuming straight line extrapolations will lead to more confident lifetime estimates.